Bilateral internal carotid artery hypoplasia presenting with watershed territory infarcts - Shikhil Uppal; Ankur Chandra; Bipin Chaurasia (Radiology Case Reports, 2024)
Internal carotid artery hypoplasia is a rare vascular anomaly that can lead to various neurological symptoms due to altered cerebral blood flow. We present a case of a 36 years old female who presented to us with forgetfulness and right sided weakness. She was ultimately diagnosed with bilateral internal carotid artery hypoplasia through imaging studies. This case highlights the importance of considering vascular anomalies in patients presenting with neurological symptoms and the significance of comprehensive diagnostic evaluation for appropriate management.